The Effect of Employee Engagement and Job Satisfaction Towards Organizational Citizenship Behavior: Study on employees of PT. Angkasa Pura II SSK II Pekanbaru Airport - Fitriansyah, Muhammad Hafizd; Ningsih, Dewita Suryati; Fitri, Kurniawaty (Westscience Press, 2025)
This research aims to determine the influence of Employee Engagement and Job Satisfaction towards Organizational Citizenship Behavior at PT. Angkasa Pura II SSK II Airport Pekanbaru. The population in this study was all 63 employees. Technique sampling used in this research are sampling fed up. The data analysis method used in this research is multiple linear regression analysis using the SPSS Version 26 program. The results of the research show that there is a positive and significant influence between Employee Engagement and Organizational Citizenship Behavior. There is a positive and significant influence between Job satisfaction and organizational Citizenship Behavior. There is a simultaneous positive and significant influence between Employee Engagement and Job Satisfaction on Organizational Citizenship Behavior